ALL-IN meta-analysis: breathing life into living systematic reviews and prospective meta-analyses [version 2; peer review: 1 approved, 2 approved with reservations] - Judith ter Schure; Peter Grünwald (F1000Research)
Science is justly admired as a cumulative process (“standing on the shoulders of giants”), yet scientific knowledge is typically built on a patchwork of research contributions without much coordination. This lack of efficiency has specifically been addressed in clinical research by recommendations against avoidable research waste and for living systematic reviews and prospective meta-analysis. We propose to further those recommendations with ALL-IN meta-analysis: Anytime Live and Leading INterim meta-analysis. ALL-IN provides meta-analysis based on e-values and anytime-valid confidence intervals that can be updated at any time—reanalyzing after each new observation while retaining type-I error and coverage guarantees, live—no need to prespecify the looks, and leading—in the decisions on whether individual studies should be initiated, stopped or expanded, the meta-analysis can be the leading source of information without losing validity to accumulation bias. The analysis design requires no information about the trial sample sizes or the number of trials eventually included. So ALL-IN meta-analysis can be applied retrospectively as well as prospectively, to evaluate the evidence once or sequentially. Because the intention of the analysis does not change the validity of the results, the results of the analysis can change the intentions (‘optional stopping’ and ‘optional continuation’ based on the results so far). On the one hand: any analysis can be turned into a living one, or even become prospective and real-time by updating with new trial data and including interim data from trials that are still ongoing — without any changes in the cut-offs for testing or the method for interval estimation. On the other hand: no stopping rule needs to be enforced for the analysis to remain valid, so participating in a prospective meta-analysis does not require outside control over data collection. Hence ALL-IN meta-analysis breathes life into living systematic reviews, and offers better and simpler statistics, efficiency, collaboration and communication.